2018
DOI: 10.1021/acs.est.8b02822
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Extracellular Flavins in a Coastal Marine Basin and Their Relationship to Redox Gradients and Microbial Community Members

Abstract: The flavins (including flavin mononucleotide [FMN] and riboflavin [RF]) are a class of organic compounds synthesized by organisms to assist in critical redox reactions. While known to be secreted extracellularly by some species in laboratory-based cultures, flavin concentrations are largely unreported in the natural environment. Here, we present pore water and water column profiles of extracellular flavins (FMN and RF) and two degradation products (lumiflavin and lumichrome) from a coastal marine basin in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 72 publications
2
31
1
Order By: Relevance
“…Dissolved Mn showed positive correlations with four OTUs belonging to Desulfobacterales, Syntrophbacterales and Bathyarchaeota, while dissolved Fe was more closely related to OTUs that were affiliated to Dehalococcoidia, Anaerolineae and Planctomycetes. This result was different from the findings in San Pedro Basin (Monteverde et al 2018) where dissolved Fe exhibited close positive correlations with proteobacterial OTUs. Bacterial or archaeal OTUs showed few direct correlations with DOC and DIC, but were closely correlated to δ 13 C TOC and NH 4 + .…”
Section: Specific Linkages Between Environmental Variables and Bactercontrasting
confidence: 99%
See 1 more Smart Citation
“…Dissolved Mn showed positive correlations with four OTUs belonging to Desulfobacterales, Syntrophbacterales and Bathyarchaeota, while dissolved Fe was more closely related to OTUs that were affiliated to Dehalococcoidia, Anaerolineae and Planctomycetes. This result was different from the findings in San Pedro Basin (Monteverde et al 2018) where dissolved Fe exhibited close positive correlations with proteobacterial OTUs. Bacterial or archaeal OTUs showed few direct correlations with DOC and DIC, but were closely correlated to δ 13 C TOC and NH 4 + .…”
Section: Specific Linkages Between Environmental Variables and Bactercontrasting
confidence: 99%
“…Bacterial groups such as Anaerolineaceae, Dehalococcoidia and Desulfarculales have been linked to the degradation of recalcitrant organic compounds (Oni et al 2015b). They were mainly present in the deep layers in previous studies (Monteverde et al 2018;Qiao et al 2018) and showed positive correlations with NH 4 + , δ 13 C TOC values and humic-like FDOM in this study (Fig. 5).…”
Section: Discussionsupporting
confidence: 62%
“…All three Chloroflexi OTUs were assigned to class Dehalococcoidia, which is frequently detected from seafloor sediments and possesses genes related to hydrogen and sulfur compound oxidation with reductive dehalogenation of halogenated organic compounds [8890]. Notably, MSBL9 and Dehalococcoidia possess potential of flavin secretion in marine sediments [91], implying that these lineages also contribute to maintaining extracellular metabolite pools in hadal sediments. The single Bacteroidetes OTU was affiliated with class BD2-2, which may interact with methanotrophic archaea and sulfate-reducing bacteria in methane seep sediments [92].…”
Section: Resultsmentioning
confidence: 99%
“…Notably, Shewanella putrefaciens produced 4,400 mW m −2 with specially designed electrode materials 39 . In the environment, mediators such as flavins have been detected in marine sediments and pore waters, with the concentrations positively correlated to the concentrations of dissolved manganese, which suggests that the flavins might contribute to the reduction of insoluble manganese through extracellular electron transfer 40 .…”
Section: [H1] Exoelectrogenic Microorganismsmentioning
confidence: 99%